Knowledge and Attitude on Legalization of Abortion among Undergraduate Students - Ojha, S; Silwal, M (Journal of Gandaki Medical College-Nepal, 2018)
Background: Abortion is public health concern in many parts of the world and is also contentious issue with religious, moral, cultural and political dimensions. Awareness program has most essential role to prevent the unusual death of mothers in the world.Objectives: To assess the knowledge and attitude on legalization of abortion among undergraduate students.Methods: A cross-sectional descriptive research design was used for this study. Proportionate stratified sampling technique and simple random sampling technique was used to select the subjects. Total 90 students were chosen as a sample and structured self-administered questionnaire was used to collect data.Results: The mean age of the respondents was 19.82. Most 58 (64.40%) of the respondents were females; majority 76 (84.40%) of the respondents were of upper caste group. Most 85 (94.4%) of the respondents had adequate knowledge on legalization of abortion and majority 83 (94.30%) of the respondents had positive attitude towards legalization of abortion. The study shows that the most knowledgeable area was on concept of abortion (88.55%) and the least knowledgeable (58.00%) area was on method of abortion. Factors like age, gender, residence and educational faculty were not found to be associated with knowledge on legalization of abortion.Conclusions: Undergraduate students had good level of knowledge and attitude on legalization of abortion. Highest knowledge was present in concept of abortion and lowest in methods of abortion. More awareness program should be accessible to undergraduates in order to increase the level of knowledge. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 52-57